The origin of Dragon Boat Festival / Ong Sheau Fen - Ong, Sheau Fen (Academy of Language Studies, 2022)
The Dragon Boat Festival (iffi^tPduanwujie) is a traditional Chinese festival held on the fifth day of the fifth month of the Chinese calendar, which usually falls in May or June of the Gregorian calendar. It is believed that this festival commemorates the death of the poet and minister Qu Yuan (340-278 BC) of the ancient state of Chu during the Warring States period of the Zhou dynasty <> Qu Yuan is a member of the Chu royal house, and served in the high offices. At that time, there was an increasingly powerful neighbouring state in the vicinity of Chu State, Qin State. Seeing that the Qin state is getting powerful, in order to avoid the Chu state being swallowed up in the future, Qu Yuan advocated the state of Chu united with other neighbouring states to fight against the state of Qin. However, the emperor of Chu decided to corporate with the Qin state and Qu was banished for opposing the alliance and accused of treason. As a consequent, his was exiled. Twenty-eight years later, Qin control Ying, the Chu capital by force. In despair, Qu Yuan, on the fifth of the fifth month of lunar calendar, committed suicide by drowning himself in the Miluo River.